Cold Expansion Strengthening of 7050 Aluminum Alloy Hole: Structure, Residual Stress, and Fatigue Life - Qi Li; Qichao Xue; Quansheng Hu; Ting Song; Yonghui Wang; Siyang Li (International Journal of Aerospace Engineering)
The 7050 aluminum alloy orifice plate is extruded and strengthened by the cold expansion process of slotted bushing holes. A three-dimensional finite element model was established for cold expansion strengthening of holes, and the residual stress distribution of 7050 aluminum alloy orifice plates is studied after cold expansion. The influence of different relative extrusion amounts and different sample thicknesses on the residual stress around the sample hole was analyzed, and the relationship between the extrusion amounts and the thicknesses of the substrate and the residual stress was obtained by analysis. The research results indicate that the cold expansion process of slotted bushing holes can enhance the residual stress distribution around the hole and form a strong residual stress layer. As the amounts of extrusion increase, the residual stress tends to increase, reaching the maximum when the amounts of extrusion are 4%. The residual stress on the surface of the extrusion inlet increases with the increase in the thickness of the substrate. Within the range of 3%-4% of the extrusion amounts, with the continuous increase of the extrusion amounts, the fatigue life has been substantially enhanced, and the number of fatigue life is more than 3 times that of the empty plate fatigue test.